Meta Analysis Study: Effect of STEM (Science Technology Engineering and Mathematic) towards Achievement - Ahmad Khoiri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Research on the effect of STEM integration on learning outcomes is determined through Effect Size (ES). The ability of researchers to summarize articles on statistical domains (Mean, SD, Pre Test, Post Test, Chi Square, Coefficient r, t-Value, P-value) that are reviewed to place research positions as consideration in the needs analysis and introduction. Literature research results obtained from 42 articles sourced from Google Scholar, Science Direct and Elvesier relating STEM and learning outcomes. Meta analysis study based on the form of STEM learning outcomes, Integration Type, Publication Year, Education Level and ES value. The results of data analysis show the greatest use of STEM in the integration of Project Based Learning (PjBL) from the 8 integrations formed. Most of the research conducted at the level of Higher Education 47.6% had an effect on the learning outcomes of S-T-E-M. The ES value obtained ranges from 0.684 to 4.44 with an average of 0.93 high categories and ES determination R2 = 0.7458 or 74.58% contributing to the influence of STEM on learning outcomes. Based on data analysis, the learning outcomes are in the form of conceptual understanding, 21st century students' motivation and skills which include critical thinking skills, creative and problem solving as a provision for career skills preparedness in the future by solving global issues.